Force‐Induced Molecular Isomerization for the Construction of Multicolor Luminescent Segmented Molecular Crystals. Issue 2 (14th November 2021) - Guo, Yongxian; Wu, Aoli; Qiu, Changkun; Ge, Fayuan; Jiang, Yifei; Gong, Yanjun; Hu, Qiongzheng
Abstract: Multicolor luminescent segmented materials have attracted tremendous research interest due to their potential applications as barcoding materials in information security and anti‐counterfeiting. Although much effort has been devoted to the preparation of photonic barcodes based on different light‐emitting materials, the rational design of barcoding materials with well‐controlled emission color and length at desired position remains a challenge. Here, a novel strategy to fabricate multicolor luminescent segmented 1D molecular crystals is reported by manipulating the molecular conformation and intermolecular interactions of the mechanochromic crystals, which are assembled from a rationally designed twisting conjugated molecule. The emission color of these mechanochromic crystals changes from green to orange with the mechanism of synergy effect of force‐induced molecular isomerization from trans to cis state and molecular packing changes from cross to parallel, which is revealed by single crystal X‐ray diffraction. Multicolor luminescent segmented 1D microribbons are fabricated by applying precisely controlled forces by tapping mode atomic force microscope, which shows the encoding capability. These findings provide a new method that allows the controllable fabrication of segmented materials with tunable emission color and length at desired position toward barcoding applications. Abstract : A novel strategy to construct a multicolor luminescent segmented 1D molecular crystal is successfully developed by manipulating the molecular conformation and interactions of the mechanochromic materials that are assembled from a twisting donor (D)‐acceptor (A) molecule.